2017
DOI: 10.5039/agraria.v12i1a5422
|View full text |Cite
|
Sign up to set email alerts
|

Adequação do teste de envelhecimento acelerado para avaliação do vigor de sementes de leucena

Abstract: RESUMOLeucaena leucocephala (Lam.) de Wit. (Fabaceae) é uma leguminosa arbórea indicada para a composição de sistemas agroflorestais e alimentação de animais em regiões de clima semiárido. Dada sua importância, objetivou-se com este estudo adequar a metodologia do teste de envelhecimento acelerado para avaliação do vigor das sementes. Para tanto, procederamse a execução de testes de envelhecimento acelerado à temperatura de 41 °C durante 0, 48, 72 e 96 h em lotes de sementes, com avaliação da porcentagem de ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…With the increase of the temperature and longer time spent in aging conditions, the germination tends to be negatively affected (Flavio and Paula 2010). However, this information cannot be generalized, since in the present study, as found by Araújo et al (2017) in leucene seeds, some lots increased the germination percentage with the expansion of the period of exposure to accelerated aging. This fact is explained due to the greater stress tolerance of these lots, thus giving them greater physiological potential.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…With the increase of the temperature and longer time spent in aging conditions, the germination tends to be negatively affected (Flavio and Paula 2010). However, this information cannot be generalized, since in the present study, as found by Araújo et al (2017) in leucene seeds, some lots increased the germination percentage with the expansion of the period of exposure to accelerated aging. This fact is explained due to the greater stress tolerance of these lots, thus giving them greater physiological potential.…”
Section: Resultscontrasting
confidence: 61%
“…It can be observed that there was a significant increase in the moisture content of the seeds after the traditional accelerated aging test (Table 3), as observed by Araújo et al (2017) in leucene seeds. Marcos Filho (2016) states that the moisture content corresponds to the equilibrium point, which increases with the elevation of the relative humidity of the air and vice-versa.…”
Section: Resultsmentioning
confidence: 69%
“…It was also verified that seed deterioration increases with the increment of the exposition period to the accelerated aging test, once the reduction of germination was verified within each temperature tested (Araújo et al 2017). Frandoloso et al (2017) sustain that temperature increment promotes more drastic effects in germination than the extension of the exposition period to accelerated aging, as we verified at a temperature of 45 o C. Peng et al (2011) found in aging that high temperatures and high relative humidity caused lower selectivity of plasma membranes, in addition to reactive oxygen species triggering lipid peroxidation.…”
Section: Discussionmentioning
confidence: 76%
“…seeds, at different temperatures and aging times, found a (A) (B) S11 = 85,9382 -0,5671x R 2 = 0,96 S12 = 75,9640 + 0,9697x -0,0268x 2 + 0,00011x 3 R 2 = 0,93 S13 = 64,9543 + 1,7911x -0,0469x 2 + 0,0002x 3 R 2 = 0,99 S14 = 87,39885/(1 + e 0,08692(x -54,71915) ) R 2 = 0,99 S15 = 78,58186/(1 + e 0,05619(x -69,81257) ) R 2 = 0,96 S11 = 75,0338 -0,0873x -0,0033x 2 R 2 = 0,90 S12 = 81,1968 -0,0169x -0,0045x 2 R 2 = 0,96 S13 = 76,4203 -0,0025x -0,0036x 2 R 2 = 0,92 S14 = 74,8360 + 1,1674x -0,0287x 2 + 0,0001x 3 R 2 = 0,91 S15 = 73,9777 + 0,9725x -0,0289x 2 + 0,0001x 3 R 2 = 0,95 significant reduction in germination. In Leucaena leucocephala seeds, germination declined in the different lots, increasing the accelerated aging time (Araújo et al, 2017). Considering three P. moniliformis seed lots, Aquino et al (2018) concluded that aging for 24 h at 41°C was the most appropriate condition to separate seed lots into different vigor levels since it produced results similar to those obtained when classifying the initial quality of the lots.…”
Section: Resultsmentioning
confidence: 89%